The effect of diet and acute starvation on the deiodination of thyroxine and triiodothyronine in the thyroidectomized rat - Nathanielsz, P. W. (1970)
1. General agreement exists that the level of thyroid function is depressed by starvation. The virtually complete cessation of biliary-faecal thyroxine loss in the starved animal makes the significance of this reduction difficult to assess in physiological terms. 2. Deiodination of [(131)I]thyroxine was investigated in thyroidectomized rats. Thus central feed-back effects were eliminated and the changes in peripheral utilization of thyroxine could be observed. The simultaneous use of [(125)I] sodium iodide permitted changes in renal handling of iodide to be taken into consideration. 3. Rats fed oxoid (Oxo Ltd. diet 41 B) deiodinated a significantly greater proportion of thyroxine in the 24 hr after injection of a tracer dose of [(131)I]thyroxine than did the starved or glucose-fed rat. [(131)I]triiodothyronine was also probably deiodinated at a faster rate in oxoid-fed rats than in starved or glucose-fed rats. 4. Thyroxine was deiodinated at a faster rate by starved rats than by rats fed glucose. 5. Thyroxine disappeared significantly faster from the blood in oxoid-fed than in the starved or glucose-fed rat. Thyroxine also disappeared faster from the blood in the starved rat than in the glucose-fed rat over 24 hr. 6. These results are discussed in relation to previous findings of depressed pituitary—thyroid function in starvation.